Mobile application for event updates - Vanteddu, Satya Sagar (Kansas State University, 2016)
It is really tough for someone new to a place to search for new addresses or navigate from one building to another. Further, it would help the user to keep track of event at each building/location in the app itself rather than noting them down on a piece of paper. Keeping these in mind, the idea is to develop a mobile app through which one can easily search for addresses/buildings which might not be available in google maps and also should be getting updates regarding the events at that location. This can be achieved by storing the latitudes and longitudes of each building or any specific location through the website which in turn is updated in the mobile application. The user can further check the events at each building which will be updated from the website. The application is divided into two parts, user module and admin module. The user would be using a mobile app to perform the required operations while the admin is responsible for storing the locations and events. Since there are a huge percentage of both android, iOS and windows users these days, it would be beneficial to build a hybrid app which would work cross platform rather than building a native app. I would be using the native browsers of these operating systems to achieve this. The admin module is a website through which locations and events at specified locations can be stored based on dates in an attached relational database. This module can only be accessed by authorized users and is responsible for all the updates visible for the mobile app user. The completely developed app can be used by any organization or institution to be used by their staff/students, etc.
Keywords: mobileappforeventupdates